2014
DOI: 10.1002/ejlt.201400152
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the fatty acid composition of phospholipids and triacylglycerols of brown trout

Abstract: Seasonal variations on phospholipid (PL) and triacylglycerol (TG) fatty acid (FA) compositions in muscles of Salmo trutta macrostigma were investigated by gas chromatography (GC) using the method described by Folch. The total lipid of the muscle was extracted using chloroform/methanol (2:1, v/v) and was separated into TG and PL using thin layer chromatography (TLC). A total of nineteen and sixteen different fatty acids were determined in TG and PL, respectively. The distributions of SSFAs (saturated fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…Fish polar lipids are commonly considered as a physiologically crucial lipid class that are rich in LC-PUFA, mostly in DHA and, to a lesser extent, in EPA [19,37,39]. Indeed, percentages of DHA and EPA in PL of various wild marine and freshwater species ranged as 11.5-55.7% and 2.6-14.6%, with average values of 31.4% and 7.4%, respectively [40][41][42][43][44][45][46]. The average levels of EPA and DHA in the fish species from our study coincided with the above ranges, except the EPA value of whitefish, 16.6%, which was a bit higher than the known values.…”
Section: Content Of Essential Lc-pufa In Fish Pl and Tagmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish polar lipids are commonly considered as a physiologically crucial lipid class that are rich in LC-PUFA, mostly in DHA and, to a lesser extent, in EPA [19,37,39]. Indeed, percentages of DHA and EPA in PL of various wild marine and freshwater species ranged as 11.5-55.7% and 2.6-14.6%, with average values of 31.4% and 7.4%, respectively [40][41][42][43][44][45][46]. The average levels of EPA and DHA in the fish species from our study coincided with the above ranges, except the EPA value of whitefish, 16.6%, which was a bit higher than the known values.…”
Section: Content Of Essential Lc-pufa In Fish Pl and Tagmentioning
confidence: 99%
“…Triacylglycerols are considered to be relatively poor in LC-PUFA and preferably accumulate monoenoic C16-22 FA [18,19,37]. According to the available data, levels of DHA and EPA in fish TAG varied in intervals of 2.3%-23.3% and 1.1%-14.1%, with average values of 8.8% and 5.3%, respectively [40][41][42][43][44][45][46]. The percentages of both EPA and DHA of TAG in the fish species from our study well coincided with the above ranges (Table 5).…”
Section: Content Of Essential Lc-pufa In Fish Pl and Tagmentioning
confidence: 99%
“…Furthermore, the seasonal variations of the factors mentioned could be effective in changing the FA composition of fish (Kayhan et al 2015;Kaçar and Başhan 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid and FA compositions of fish can differ depending on seasonal changes, along with food, age, sex and spawning period (Christiansen et al, 1989). The latest studies have reported that lipid composition was affected by seasonal variations (Kayhan et al, 2015;Kaçar et al, 2016). In the same fish species, the total lipid contents of the gonad and liver changed from 1.32 to 4.90% and from 1.32 to 3.94%, respectively (Kaçar and Başhan, 2016).…”
Section: Fat Analysismentioning
confidence: 99%